2003
DOI: 10.2320/matertrans.44.692
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Boron-strontium Interactions on Eutectic Modification in Al-10 mass%Si Alloys

Abstract: The effects of boron and strontium interactions on the eutectic silicon in hypoeutectic Al-Si alloys have been studied. Samples were prepared from an Al-10 mass%Si base alloy with different Al-B additions, alone and in combination with strontium. In alloys containing no strontium, boron additions do not cause modification of the eutectic silicon, while in strontium containing alloys, boron additions reduce the level of modification of the eutectic silicon. Thermal analysis parameters and eutectic silicon micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 7 publications
1
7
0
1
Order By: Relevance
“…Şöyle ki; literatürde [24], [25], stronsiyum ilavesinin ötektik reaksiyon süresince açığa çıkan ısının artmasına ve bu nedenle ikili alaşıma göre ötektik dönüşüm sıcaklığının düşmesine, ötektik noktanın sağa yani daha yüksek silisyum oranına doğru kaymasına ve dolayısıyla çekirdeklenmenin daha düşük sıcaklıkta başlamasına neden olduğu ifade edilmektedir. Çekirdek büyüme sıcaklığındaki düşmenin Al-Si ötektik çekirdeklerinin etrafındaki katılaşmayı engellemesi, bir başka deyişle çekirdek büyümesini azaltması nedeniyle ötektik silisyum parçacıklarının daha ince taneli kalmasına neden olduğu ileri sürülmektedir [31], [32]. Stronsiyum ilavesi ile özellikle silisyumca zengin fazların morfolojisinin değişmesi stronsiyumun daha ziyade silisyum parçacıkları içinde çözündüğünün de bir göstergesi olabilir.…”
Section: Deneysel çAlışmaunclassified
“…Şöyle ki; literatürde [24], [25], stronsiyum ilavesinin ötektik reaksiyon süresince açığa çıkan ısının artmasına ve bu nedenle ikili alaşıma göre ötektik dönüşüm sıcaklığının düşmesine, ötektik noktanın sağa yani daha yüksek silisyum oranına doğru kaymasına ve dolayısıyla çekirdeklenmenin daha düşük sıcaklıkta başlamasına neden olduğu ifade edilmektedir. Çekirdek büyüme sıcaklığındaki düşmenin Al-Si ötektik çekirdeklerinin etrafındaki katılaşmayı engellemesi, bir başka deyişle çekirdek büyümesini azaltması nedeniyle ötektik silisyum parçacıklarının daha ince taneli kalmasına neden olduğu ileri sürülmektedir [31], [32]. Stronsiyum ilavesi ile özellikle silisyumca zengin fazların morfolojisinin değişmesi stronsiyumun daha ziyade silisyum parçacıkları içinde çözündüğünün de bir göstergesi olabilir.…”
Section: Deneysel çAlışmaunclassified
“…The impact of B and Sr additions on grain refinement and modification has been reported by several investigators [29][30][31][32][33][34]. The present paper reports the results of additional experiments where B and Sr are added to the popular AlSi7Mg0.3 alloy either individually or together in an effort to identify a sound and cost-effective melt treatment practice for hypoeutectic Al-Si-based foundry alloys.…”
Section: Introductionmentioning
confidence: 75%
“…The same group of researchers showed that the addition of boron has no effect on the eutectic growth temperature which usually decreases with modification, 66 where they showed that the recovered Sr levels were similar to the nominal addition levels in strontium-added samples in the absence of boron. these experiments and the master alloys and addition levels used will also be discussed.…”
Section: Interaction Of Grain Refiners and Modifying Agentsmentioning
confidence: 98%